PERAN EKOFEMINISME BAGI PEREMPUAN DALAM PRAKTIK DAUR ULANG SAMPAH BAGI MASYARAKAT - Kartika, Silvia Dwi; Harahap, Rahma Hayati (Indonesian Journal of Conservation, 2023)
In facing the global environmental crisis, women play an important role as the front guard in protecting the earth and overcoming the waste problem. Waste management is an important aspect in efforts to protect the environment. The practice of recycling waste is a very important step in reducing the negative impact of waste on our ecosystem. The practice of recycling waste is a key step in reducing the negative impact of waste on the environment. This journal discusses the role of women in waste recycling practices and their economic, social and environmental impacts. The concept of ecofeminism is also used to describe the special relationship between women and nature. With examples of real recycling practices from communities, this Journal illustrates how women can turn waste into valuable goods and contribute to environmental conservation. In this research process, I used a qualitative descriptive research method by collecting data through questionnaires and interviews with the younger generation and other housewives. The research results show that understanding and recognizing the role of women in waste recycling practices can promote a better culture of environmental care.Keywords:   Recycling, Ecofeminism, Women